Penerapan Hukum Disiplin Prajurit Tentara Nasional Indonesia di Pangkalan Korps Marinir Surabaya - Pattiasina, Patrick; Yustitianingtyas, Levina (Legal Standing : Jurnal Ilmu Hukum, 2025)
As the largest archipelagic state, Indonesia possesses a vast maritime territory that is both strategically significant and rich in natural resources but also vulnerable to various global threats. The Indonesian National Armed Forces (TNI), including the Marine Corps under the Navy (TNI AL), play a crucial role in safeguarding national sovereignty and maintaining stability. Discipline among personnel is a key element in ensuring mission success, particularly at the Marine Base (Lanmar) Surabaya, which serves as a vital pillar of maritime defense. Military disciplinary law for TNI personnel is governed by various regulations, including the 1945 Constitution, Perkasal No. 13 of 2024 concerning Commanders Authorized to Impose Disciplinary Actions (Ankum) in the Navy, Perpang TNI No. 11 of 2018, and Perkasal No. 30 of 2018, which provide guidelines for imposing administrative and disciplinary sanctions on personnel. However, disciplinary violations persist, highlighting challenges in implementing these regulations in practice. This study focuses on the application of military disciplinary law at Lanmar Surabaya, analyzing its effectiveness in maintaining professionalism and performance among personnel, as well as identifying obstacles encountered in its implementation. Using a juridical-empirical approach, this research combines primary and secondary data to propose solutions aimed at improving compliance with military disciplinary regulations. The findings of this study are expected to offer strategic recommendations to enhance the operational success of Lanmar Surabaya in fulfilling its national defense mission.